From government control to increased transparency? Changes to quality assurance of higher education in Japan and China - Huang, F (Centre for Global Higher Education, University of Oxford, 2017)
Professor Futao Huang from Hiroshima University discusses the growth of quality assurance in higher education in Japan and China.